Jean Nouvel - Casamonti, Marco; Nouvel, Jean, 1945- (Milan : Motta, 2009)
The aim of this collection is to offer a series of short monographs which, though brief, nevertheless deal with all aspects of the master's personality: works, constructed or otherwise, primary written sources, critiques and photographic interpretations. The underlying aim is to offer an in-depth, comprehensive overview targeted at anyone interested in learning about architecture including students, professionals or simply those who are interested in the subject, by providing not only basic information but also guidance in terms of gaining more insight into the subject. The volumes are dedicated to some of the best known modern and contemporary architects.
Works: Institut du Monde Arabe, Paris ; L'Opera, Lyon ; Fondation Cartier, Paris ; Palais de Justice, Nantes ; Expansion of the Museo Nacional Centro de Arte Reina Sofia, Madrid ; Agbar Tower, Barcelona ; Musée du Quai Branly, Paris ; Guthrie Theater, Minneapolis ; Brembo Science Park, Kilometro Rosso, Bergamo -- Projects: Concert House Danish Radio, Copenhagen ; Office Tower, Dhoa ; Guggenheim Foundation,Guadalajara ; Performing Arts Centre, Seoul ; La Philharmonie, Paris ; Louvre Abu Dhabi, Abu Dhabi ; Tour Signal, Paris.
Includes bibliographical references (p. 119)
In English, translated from Italian.
Keywords: Nouvel, Jean, -- 1945-